Total Synthesis and Molecular Docking study of Peptide AWVDY as an Anti-inflamation Agent - Anderson Arnold Aloanis; Jessika Maya Jovanka Najoan; Vlagia Indira Paat; Stefan Marco Rumengan; Rymond Jusuf Rumampuk (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Bioactive peptides are known for their diverse biological functions, many of which support health and well-being. In this study, we synthesized and evaluated the anti-inflammatory potential of the peptide AWVDY, derived from oyster (Crassostrea rivularis). The synthesis was performed using the solid-phase peptide synthesis (SPPS) method, applying the Fmoc strategy on 2-chlorotrityl chloride (2-CTC) resin, and achieved a high yield of 95.83%. The resulting peptide was characterized using Time-of-Flight Mass Spectrometry (TOF-MS), which detected a peak at m/z [M+H⁺] 653.1418, consistent with the expected molecular formula C₃₂H₄₀N₆O₉. This was further validated by analytical HPLC, showing a retention time of 22.596 minutes. Molecular docking studies indicated that AWVDY binds favorably to the pro-inflammatory cytokines TNF-α and Interleukin-6, with binding affinities of -10.360, -10.430, and -8.960 kcal/mol, respectively. These findings suggest that AWVDY may act as a dual-target peptide capable of modulating inflammatory pathways, highlighting its potential as a promising candidate for the development of new anti-inflammatory therapeutics.